Determinants Of Investment Decisions Millenial and Zilenial Generation - Yessi Nesneri; Ulfiah Novita; Nursri Hayatina (Fakultas Ekonomi Universitas Kadiri, 2026)
Investment is an activity of investing valuable assets to generate profits. This research aims to analyze the influence of financial literacy, financial behavior, investment motivation, risk perception, and investment experience on investment decisions of the millennial and zilennial generations using Structural Equation Modeling (SEM) - Partial Least Square (PLS) analysis. The results of the study indicate that financial behavior, investment motivation and risk perception have a significant influence on the investment decisions of the millennial and zilennial generations. Meanwhile, financial literacy and investment experience have no influence and are not significant on the investment decisions of the millennial and zilennial generations. Additionally, it was found that financial literacy, financial behavior, investment motivation, risk perception, and investment experience influence investment decisions by 66.5% and the remaining 33.5% is influenced by other variables not examined in this research.